Պրօկուրօրեան բարենորոգումների փորձ Մայր Աթոռում եւ կաթողիկոս Ներսէս Ե. Աշտարակեցին - Օհանեան, Հրանտ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
17 апреля 1843 г. Нерсес Аштаракеци был избран Католикосом Всех Армян (1843—1857). Новоизбранный Католикос Армении в июне покидает Бессарабию и прибывает в Санкт-Петербург, где должно было состояться утверждение избрания Католикоса Николаем I. Этот, задуманный как краткий, визит из-за нездоровья Верховного Патриарха, оказался довольно долгим – от начала августа до мая следующего года. Интересные сведения о развитии событий в этот период сохранились в Матенадаране имени Маштоца, в частности в архиве Александра Ерицяна, которые дают новые и важные подробности о положении дел в Эчмиадзине во время отсутствия армянского католикоса в кафедральном соборе Святого Эчмиадзина, о деятельности Эчмиадзинской патриархии и прокурора Синода Степана Матинова (Матинянца), приведшей к острым противоречиям и в конечном итоге его отстранению от должности. On April 17, 1843, Nerses of Ashtarak was elected Catholicos of All Armenians (1843—1857). The newly elected Catholicos of All Armenians left Bessarabia in June and arrived in St. Petersburg, where Nicholas I was to confirm the election of the Catholicos. However, due to the ill health of the Supreme Patriarch, this seemingly short visit from early August to May of the following year turned into a long layover. Remarkable information about the Mother See of Holy Etchmiadzin and church affairs of that period has been preserved in the Mashtots Matenadaran, particularly in the archive of Alexander Yeritsyan, which provides new and important details about the situation in the Mother See during the absence of the Armenian Catholicos, the activity of Stepan Matinov (Matinyants), procurator of Holy Etchmiadzin Brotherhood and Synod, which led to sharp contradictions and eventually to his removal from office
Keywords: Պատմաբանասիրութիւն